Production and biotechnological potential of extracellular polymeric substances from sponge-associated Antarctic bacteria - Caruso, Consolazione; Rizzo, Carmen; Mangano, Santina; Poli, Annarita; Di Donato, Paola; Finore, Ilaria; Nicolaus, Barbara; Di Marco, Gaetano; Michaud, Luigi; Lo Giudice, Angelina (Applied and Environmental Microbiology, 2018)
Four sponge-associated Antarctic bacteria (i.e. Winogradskyella spp. CAL384 and CAL396, Colwellia sp. GW185 and Shewanella sp. CAL606) were selected for the highly mucous appearance of their colonies on agar plates. The production of extracellular polymeric substances (EPSs) was enhanced by a step-by step approach varying the carbon source, substrate and NaCl concentrations, temperature and pH. The EPSs produced under optimal conditions were chemically characterized, resulting in a moderate carbohydrate content (range 15-28%), and the presence of proteins (range 3-24%) and uronic acids (range 3.2-11.9%). The chemical hydrolysis of the carbohydratic portion revealed galactose, glucose, galactosammine and mannose as principal constituents. The potential biotechnological applications of the EPSs were also investigated. The high protein content in the EPSs from Winogradskyella sp. CAL384 was probably responsible for the excellent emulsifying activity towards tested hydrocarbons, with stable emulsion index (E24) higher than those recorded for synthetic surfactants. All EPSs tested in this work improved the freeze-thaw survival ratio of isolates, thereby suggesting that they may be exploited as cryoprotection agents. The addition of a sugar in the culture medium, by stimulating the EPS production, also allowed isolates to grow in the presence of higher concentrations of mercury and cadmium. This finding was probably dependent on the presence of uronic acids and sulfate groups, which can act as ligands for cations, in the extracted EPSs.